THE ASEANâINDIA FREE TRADE AREA AND DESIGN OF FUTURE REGIONAL TRADING ARCHITECTURE IN THE ASIAâPACIFIC REGION - hidayat, Agus Syarif (P2E-LIPI, 2015)
This paper discusses the role of the ASEANâIndia Free Trade Area (AIFTA) in designing future regional trading architecture (RTA). To date, the negotiations on future regional trading architecture in the AsiaâPacific region have split into two blocs: the Trans-Pacific Partnership (TPP) and the Regional Comprehensive Economic Partnership (RCEP). By considering some essential factors, it would be to the advantage of AIFTA members to focus on negotiations under the RCEP rather than the TPP. There are at least three ways in which the AIFTA could play a significant role in the:â) course of future RTA in the AsiaâPacific region: strengthening unity of the RCEP; redressing power imbalances among RCEP participating countries; and becoming a hub for other regions.